2013
DOI: 10.1038/leu.2013.285
|View full text |Cite
|
Sign up to set email alerts
|

In vitro generation of mature, naive antigen-specific CD8+ T cells with a single T-cell receptor by agonist selection

Abstract: Peripheral blood T cells transduced with a tumor-specific T-cell receptor (TCR) face problems of auto-reactivity and lack of efficacy caused by cross-pairing of exogenous and endogenous TCR chains, as well as short term in vivo survival due to activation and growth factor-induced differentiation. We here studied an alternative strategy for the efficient generation of naive CD8(+) T cells with a single TCR. TCR-transduced human postnatal thymus-derived and adult mobilized blood-derived hematopoietic progenitor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
46
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(51 citation statements)
references
References 44 publications
5
46
0
Order By: Relevance
“…Simultaneous recognition of the cognate MHC-peptide complex by the TCR (signal 1) and CD80 or CD86 by CD28 (signal 2) results in T cell activation, proliferation, and differentiation [10,11] . In addition to cytokine production, PD-1 and CTLA-4 are inducibly expressed on T cells following a TCR signal, and subsequent binding of the TCR to one of these co-inhibitors results in cell cycle arrest and termination of T cell activation [12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneous recognition of the cognate MHC-peptide complex by the TCR (signal 1) and CD80 or CD86 by CD28 (signal 2) results in T cell activation, proliferation, and differentiation [10,11] . In addition to cytokine production, PD-1 and CTLA-4 are inducibly expressed on T cells following a TCR signal, and subsequent binding of the TCR to one of these co-inhibitors results in cell cycle arrest and termination of T cell activation [12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…Current in vitro iPSC differentiation methods employ strong TCR signaling triggered by either anti-CD3 or anti-TCR antibodies (Nishimura et al, 2013; Vizcardo et al, 2013) or by agonist peptides (Snauwaert et al, 2014). However, T cells induced by TCR stimulation or high-affinity peptides are generally incompetent functionally or are driven into unconventional T cell lineages, including regulatory T cells, natural killer (NK) T cells, and CD8αα + T cells (Takada et al, 2017; Yamagata et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we have shown that in cultures initiated with HPCs transduced to express a TCRαβ, mature CD27 + CD1a − T cells are virtually absent, but addition of the agonist peptide in the presence of the restricting HLA antigen induces maturation 27 . Here, antigen-dependent maturation is unlikely as CEA expression analysis on these cultures with qPCR was consistently negative (data not shown).…”
Section: Resultsmentioning
confidence: 89%
“…We previously reported that mono-specific TCR-transgenic cells lacking endogenous rearrangements can be generated from cord blood hematopoietic progenitor cells (HPCs) 27 . This method is based on allelic exclusion, a phenomenon that occurs physiologically in the thymus and that ensures that each T cell successfully rearranges only a single TCRβ locus.…”
Section: Introductionmentioning
confidence: 99%